2011
DOI: 10.1017/s1355617711001408
|View full text |Cite
|
Sign up to set email alerts
|

Neurocognitive Effects of HIV, Hepatitis C, and Substance Use History

Abstract: HIV-associated neurocognitive dysfunction persists in the highly active antiretroviral therapy (HAART) era and may be exacerbated by comorbidities, including substance use and hepatitis C virus (HCV) infection. However, the neurocognitive impact of HIV, HCV, and substance use in the HAART era is still not well understood. In the current study, 115 HIV-infected and 72 HIV-seronegative individuals with significant rates of lifetime substance dependence and HCV infection received comprehensive neuropsychological … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
60
0
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 65 publications
(69 citation statements)
references
References 112 publications
6
60
0
3
Order By: Relevance
“…Detectable HIV-RNA has been associated with reduced executive functioning, verbal fluency, and memory [48]. In our population, only 2 of 13 HAD patient had efficient treatment with undetectable HIV-RNA; the other 11 were untreated or not efficiently treated, and had detectable viral load.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…Detectable HIV-RNA has been associated with reduced executive functioning, verbal fluency, and memory [48]. In our population, only 2 of 13 HAD patient had efficient treatment with undetectable HIV-RNA; the other 11 were untreated or not efficiently treated, and had detectable viral load.…”
Section: Discussionmentioning
confidence: 72%
“…In addition, HIV/HCV coinfection is associated with poorer neurocognitive outcomes than infection with HIV alone [54][55][56]. Devlin et al [48] found significant associations between neurocognitive deficits and HIV load, HCV coinfection and substance abuse. Forton showed elevated frontal white matter myoinositol/creatine in patients with histologically mild liver disease due to HCV infection studied with cerebral proton magnetic resonance spectroscopy [57].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, we examined the associations between occupational and social resilience and neurocognitive functioning metrics found to be significant in the previous step by entering age, education, HIV status, depressive symptoms, and PTSD symptoms in step one of a hierarchical regression model given the known effect of these variables on neurocognitive performance (Devlin et al, 2012; McClintock et al, 2010; Scott et al, 2015), and then entering the neuropsychological variable in the second step. Regression coefficients for the second step of each model, as well as the R 2 change, are reported in Table 3.…”
Section: Resultsmentioning
confidence: 99%
“…Next, we proceeded with a focused analysis of the significant associations evident in the univariate correlations by conducting a series of hierarchical multivariate regressions. As age, education, and HIV status are known to predict neurocognitive performance (Devlin et al, 2012), as well as depressive symptoms (McClintock, Husain, Greer, & Cullum, 2010) and Posttraumatic Stress Disorder (PTSD; American Psychiatric Association, 2000; Scott et al, 2015), these variables were entered in the first step to capture within-source variability. Then, neuropsychological variables were entered in the second step to measure between-source variability, thereby isolating the variance explained by our neuropsychological variables.…”
Section: Analytic Strategymentioning
confidence: 99%
“…Overall, most studies reported that the HIV/HCV co-infected patients were generally more impaired than HIV and HCV monoinfected patients and controls Ciccarelli et al, 2013;Clifford, Evans, Yang, & Gulick, 2005;Devlin et al, 2012;von Giesen et al, 2004;Hinkin et al, 2008;Letendre et al, 2005;Martin et al, 2004;Parsons et al, 2006;Rempel et al, 2013;Ryan, Morgello, Isaacs, Naseer, & Gerits, 2004;Sun et al, 2013;Vivithanaporn et al, 2012). Other studies found no differences on cognitive performance between HIV/ HCV and HIV mono-infected groups (Aronow, Weston, Pezeshki, & Lazarus, 2008;Thiyagarajan et al, 2010), between HIV/HCV and HCV mono-infected groups (Clifford et al, 2009;Perry et al, 2005), and between HIV/HCV and both HIV and HCV mono-infected groups (Thein et al, 2007).…”
Section: Cognitive Impairmentmentioning
confidence: 98%